Oh I think I figured it out.
6 ( 1 + h/2 )
6 x 1 = 6
Then to multiply fraction we do:
6/1 * h/2
= 6 * h = 6h
1 * 2 = 2
6h / 2 = 3h
= 6 + 3h
I needed to turn 6 into the fraction 6/1
Is that correct?
Hi all,
So I am going through a workbook and it has this question:
6 ( 1 + h/2 )
This is how I did it:
6 x 1 = 6
6 x h = 6h
6 x 2 = 12
= 6 + 6h/12
= 6 + h/2
But apparently the answer is:
6 + 3h
Can someone tell me where I wen't wrong?
The text book doesn't explain it and I am so confused.
Thanks
Oh I think I figured it out.
6 ( 1 + h/2 )
6 x 1 = 6
Then to multiply fraction we do:
6/1 * h/2
= 6 * h = 6h
1 * 2 = 2
6h / 2 = 3h
= 6 + 3h
I needed to turn 6 into the fraction 6/1
Is that correct?